Comparison of transgenic Bt rice and its non‐Bt counterpart in adaptability to nitrogen deficiency. Issue 3 (17th April 2018) - Jiang, Yang; Ling, Lin; Zhan, Ming; Li, Chengfang; Cao, Cougui
Abstract: Resistances of newly bred Bacillus thuringiensis ( Bt ) crops have been dramatically improved because of the effective and high expression of Bt protein in the plant. However, poorer adaptabilities to environmental stresses were observed in some Bt crops compared to their non‐ Bt counterparts. The biological reasons for the poorer adaptabilities were still unclear. A nitrogen (N) deficiency experiment was conducted to investigate variations in growth and physiology characteristics of a newly bred Bt rice [ Oryza sativa L. line MH63 ( Cry2A* )] compared to its non‐ Bt counterpart MH63. MH63 ( Cry2A* ) showed lower grain yields and lower biomass under low N levels compared to MH63. Earlier leaf senescence associated with disorder in protein metabolism was observed in MH63 ( Cry2A* ) when the N concentration was lower than 13.50 mg g −1 in MH63 ( Cry2A* ) leaves and the ratio of Bt protein to soluble protein (BT : SP) was higher than 2203 μg g −1 in MH63 ( Cry2A* ) leaves. The lower grain yield, the lower biomass and the earlier leaf senescence associated with disorder in protein metabolism in MH63 ( Cry2A* ) were correlated to the high BT : SP in MH63 ( Cry2A* ) leaves. The results suggest that MH63 ( Cry2A* ) has a poorer adaptability to N deficiency compared to its non‐ Bt counterpart MH63. This poorer adaptability might be related to the high Bt protein expression in MH63 ( Cry2A* ).